Design of a true moving bed reactor for the direct synthesis of dimethyl carbonate - B. A. V. Santos (2015)
In the present work is proposed the direct synthesis of dimethyl carbonate (DMC) using a true moving bed reactor (TMBR) to enhance the equilibrium yield. A methodology to design the TMBR is proposed, concerning the maximization of reaction conversion and DMC purity at the outlet stream, and the minimization of the desorbent consumption, together in a single-objective function. The design is supported by numerical simulation, which was based on the experimental data collected from our previous works: mass transfer, adsorption over zeolite 3A, reaction kinetics over cerium oxide, and reaction equilibrium. Besides, the design is also supported by the volume separation method and contour maps of relevant performance variables inside the separation region. In addition, the potentiality and weaknesses of a TMBR process, for the DMC production, are discussed. The TMBR here proposed allows a complete separation between water and DMC in extract and raffinate streams, together with a conversion of carbon dioxide around 6% at 30 MPa and 363 K.